2021
DOI: 10.1016/j.ijcard.2020.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury and risk factors for mortality in patients with COVID-19 pneumonia

Abstract: Background Coronavirus disease 2019 (COVID-19) pneumonia tends to affect cardiovascular system and cause cardiovascular damage. This study aimed to explore the prevalence of myocardial injury and risk factors for mortality in patients with COVID-19 pneumonia. Methods 224 consecutive patients with confirmed diagnosis of SARS-CoV-2 infection and definite outcomes (discharge or death) were retrospectively analyzed. Laboratory results including myocardial biomarkers, oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
0
35
1
Order By: Relevance
“…Direct myocardial damage by the virus should also be considered despite the fact that undisputable localization of SARS-CoV-2 within cardiomyocytes has been not proven among the limited number of autopsies in COVID-19 ( [10] , [11] , [12] , [13] , [14] ). The presence of cardiovascular risk factors or cardiac disease, both pre-existing and new, is related to poor prognosis ( [15] , [16] , [17] , [18] ). Despite the detection of the new CVD appears of paramount importance for in-hospital management and clinical course, data from a systematic evaluation has been not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Direct myocardial damage by the virus should also be considered despite the fact that undisputable localization of SARS-CoV-2 within cardiomyocytes has been not proven among the limited number of autopsies in COVID-19 ( [10] , [11] , [12] , [13] , [14] ). The presence of cardiovascular risk factors or cardiac disease, both pre-existing and new, is related to poor prognosis ( [15] , [16] , [17] , [18] ). Despite the detection of the new CVD appears of paramount importance for in-hospital management and clinical course, data from a systematic evaluation has been not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…( 4 , 5 ) In accordance, a remarkable proportion of patients suffering from Covid-19 experienced a certain degree of myocardial injury exacerbating their clinical course and worsening their prognosis. ( 6 ) However, previous report showed that Covid-19 pandemic and Governments' harsh measures to contain the contagion were associated with a reduction of hospital admission rates for ACS and percutaneous coronary intervention (PCI) procedures. ( [7] , [8] , [9] ) In parallel, it was observed an increased incidence of out-of-hospital cardiac arrests and a remarkable delay of emergency system activation for ST segment-elevation myocardial infarction (STEMI).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data showed that serious cardiac events were more common in critically ill patients with cardiac injury compared to those without cardiac injury, suggesting that cTn elevation does have cardiovascular disease manifestations and consequences [ 8 ]. Even though speculations on the possible existence of a direct virus-mediated myocardial injury have been proposed, most of the evidence, including the one here provided by Yang et al [ 9 ], suggests that the most plausible mechanism might be secondary to the systemic inflammation caused by SARS-CoV-2. As the COVID-19 pandemic continues to place healthcare systems under immense stress, the need to identify patients who are at greater risk since the early stage of hospitalization is of paramount importance for front line physicians.…”
mentioning
confidence: 88%
“…In this issue, Yang et al [ 9 ] provide an interesting report on the prevalence of myocardial injury, defined by the detection of a rise in cardiac troponin I (cTnI) above the 99th-percentile upper reference limit, in a retrospectively collected cohort of 203 laboratory-confirmed COVID-19 patients (median age 62 years, male prevalence 56%). Besides confirming that the phenomenon is not rare (37%) in the overall considered population, the Authors proved that myocardial injury was more common among those who were critically (47%) vs. moderately ill (12%) upon admission and in non-survivors (50%) vs. survivors (6%), remarking the association of cardiac injury with dismal outcomes.…”
mentioning
confidence: 99%